Analisis Pemahaman tentang Asesmen Kompetensi Minimum (AKM) pada Guru SD Dan SMP di Kabupaten Kuningan - Anna Fitri Hindriana; Asep Jejen Jaelani; Ina Setiawati; Isnaini Wulandari; Rio Priantama (Jurnal Penelitian Pendidikan IPA, 2023)
The Merdeka Belajar policy essentially aims to accelerate the achievement of national goals of education. One of the major changes in the policy is the implementation of the National Assessment (NA) which substitutes national exams and changes the focus of assessment into literacy and numeracy skills. This leads to a demand for teacher to adapt learning process and classroom assessment for facilitating students’ literacy and numeracy skills. Therefore, teacher understanding about the element in national assessment is a very important factor in the implementation of National Assessment. As the response, this study collects data about teacher understanding from 100 elementary and junior high school teachers in the Kuningan Regency area. The results shows that the elementary and junior high school teachers already have a good understanding of the objectives of NA and awareness that the implementation of NA would have an impact on providing a more varied learning and assessment experience. However, it is shown that the good understanding and awareness is not supported by capability to develop literacy and numeracy questions. The support for improving capability in making questions that align with the NA is needed in order to provide appropriate measurement and assessment of student learning outcomes and provide the basis for decision making in the classroom learning process.